Islamic theological and spiritual foundations of resilience: implications for counseling and psychotherapy with Muslims - Ssekamanya , Siraje Abdallah (2011)
Although spiritual and religious beliefs and practices play a central role in people’s lives and psychological functioning, there have not been enough attempts to study how spiritual and religious beliefs and practices could be operationalized and applied to enhance resilience. This is especially so with regards to the beliefs of Muslims. This lecture is an attempt to analyze the central beliefs and practices of Muslims in order to propose a preventive strategy that can be used in preventive/developmental settings with Muslim clients. In addition to analyzing the teachings embedded in the Qur’an and Hadith, it also considers the contributions early Muslim psychologists like al-Balkhi, Ibn Miskawayh, al-Kindi, Al-Ghazali, Ibn Taymiyyah, and Ibn Qayyim al-Jawziyyah.